Wpływ zagęszczenia podłoża w kontenerach szkółkarskich na parametry wzrostowe sadzonek sosny zwyczajnej ( Pinus sylvestris L.) - Kormanek, Mariusz; Banach, Jacek; Ryba, Michał (Leśne Prace Badawcze, 2013)
The paper presents research on influence of nursery soil compaction, composed of peat (90%) and perlite (10%), on the growth of seedlings of Pinus sylvestris grown in containers. Polyethylene nursery are containers used for the seedling production. These containers were filled with three different densities of the peat and perlite substrate (0.3, 0.5 and 0.7 g·cm -3 ). During the experiment, nursery containers were initially placed in a plastic tent for a period of two months, and then for three months further months in an open nursery field. Growth measurements for individual plants were the length of shoots and the root system, root collar diameter, root and shoot dry weight and photosynthetic rate. There was a relationship between the extent of compaction of the soil substrate and all analyzed growth parameters of seedlings. A more compact substrate adversely affected on the number of grown seedlings and their length but positively influenced the dry mass of pine seedlings.